2004
DOI: 10.1007/s00421-003-0975-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of low oxygen inhalation on changes in blood pH, lactate, and ammonia due to exercise

Abstract: The present study examined the effect of hypoxia-induced respiratory alkalosis on exercise-induced metabolic acidosis and increases in plasma lactate and ammonia levels. Six male subjects underwent exercise of increasing intensity until exhaustion: (1) in normoxia (20.9% O(2)) (=MAX), (2) in hypoxia (12% O(2)) (=HP) in which hypoxic condition had been maintained from 60 min before to 30 min after exercise, and (3) the same intensity of exercise as HP in normoxia (=SUB). Arterialized blood was drawn from a supe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
17
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 22 publications
4
17
0
Order By: Relevance
“…Grassi et al [3] hypothesized that during graded exercise in normoxia, the increased acidemia that occurred at the LT was responsible for the OMD because of a Bohr effect on the oxy-hemoglobin dissociation relationship. However, it is difficult to rationalize this mechanism to explain the concurrent leftward shifts in the LT and OMD observed in the current study because recent studies have reported that blood pH was higher under hypoxic than normoxic conditions during submaximal [9] and maximal [10] exercise. The higher blood pH was attributed to a hypoxic-induced respiratory alkalosis, even though blood lactate concentrations at the end of maximal exercise were similar under both conditions [10].…”
mentioning
confidence: 43%
See 1 more Smart Citation
“…Grassi et al [3] hypothesized that during graded exercise in normoxia, the increased acidemia that occurred at the LT was responsible for the OMD because of a Bohr effect on the oxy-hemoglobin dissociation relationship. However, it is difficult to rationalize this mechanism to explain the concurrent leftward shifts in the LT and OMD observed in the current study because recent studies have reported that blood pH was higher under hypoxic than normoxic conditions during submaximal [9] and maximal [10] exercise. The higher blood pH was attributed to a hypoxic-induced respiratory alkalosis, even though blood lactate concentrations at the end of maximal exercise were similar under both conditions [10].…”
mentioning
confidence: 43%
“…However, it is difficult to rationalize this mechanism to explain the concurrent leftward shifts in the LT and OMD observed in the current study because recent studies have reported that blood pH was higher under hypoxic than normoxic conditions during submaximal [9] and maximal [10] exercise. The higher blood pH was attributed to a hypoxic-induced respiratory alkalosis, even though blood lactate concentrations at the end of maximal exercise were similar under both conditions [10]. In summary, we observed a concurrent leftward shift in the LT and OMD during hypoxia; however the mechanism to explain this phenomenon warrants further investigation.…”
mentioning
confidence: 43%
“…At the level of skeletal muscle, in contrast to what occurs with induced MALK (117), the induction of a respiratory alkalosis by hyperventilation resulted in a slowed activation of skeletal muscle pyruvate dehydrogenase (PDH) at the onset (1 min) of submaximal exercise, which resulted in an increased accumulation of pyruvate within contracting skeletal muscle (165 When a respiratory alkalosis is induced by breathing a hypoxic gas mixture, the acid-base and metabolic changes differ markedly from a strictly hyperventilation induced respiratory alkalosis. Kato et al (148) induced a respiratory alkalosis in six subjects by having them breathe a hypoxic gas mixture of 12% O 2 for 60 min prior to exercise onset and for up to 30 min of postexercise recovery. When at rest, plasma pH increased from 7.401 to 7.437 (not significant) while [HCO 3 − ] increased significantly from 24.0 to 27.2 mmol/L (Fig.…”
Section: Experimentally Induced Respiratory Alkalosismentioning
confidence: 99%
“…Previous studies suggested that hypoxia-induced respiratory alkalosis enhances lactate accumulation in blood by exercise (Davies et al 1986;Kato et al 2004;LeBlanc et al 2002). LeBlanc et al (2002) demonstrated PFK activity to be enhanced by respiratory alkalosis and suggested that respiratory alkalosis due to hyperventilation potentiates lactate accumulation.…”
Section: Introductionmentioning
confidence: 95%